USING INTERACTIVE VIDEO TO IMPROVE STUDENTS MOTIVATION IN LEARNING ENGLISH - admin admin; Ulfatul Ma'rifah (Universitas Muhammadiyah Gresik, 2013)
Motivation becomes an important part in the successful of teaching learning process. English teachers should concern to find the way in teaching to improve students' motivation.This paper presents the use of interactive video to improve students' motivation in learning English. The writers find some studies which generate that interactive videos plays important roles to increase students motivations. It's not just the teacher play such kind of video then let students watch it, but there are such kind of video which can gain students interaction and some steps to implement it. The result is using interactive video can improve students' motivation in learning English, but this method needs some equipment which doesn't have in all school.